„ТРИУМВИРАТ ПОЭТОВ” : МИЛОШ, БРОДСКИЙ, ВЕНЦЛОВА - ВРИО, ВАЛЕНТИНА (Studia Rossica Posnaniensia, 2006)
The author describes diverse connections between three poets from Eastern Europe: Czeslaw Milosz, Joseph Brodsky and Tomas Venclova. She shows personal relationships between the members of, as she called it, the triumvirate of poets and certain similarities of their lots. Presentation of specific motifs such as: homesickness, devotion to mother tongue, or the motif of specific situation of an emigrant, connecting works of the discussed poets constitute the main part of the article.